Novel markers of inflammatory response and hepatic dysfunction in canine leishmaniasis - Tonin, Alexandre A.; Calado, Andréa M. C. [UNESP]; Bottari, Nathieli B.; Dalenogare, Diéssica; Thomé, Gustavo R.; Duarte, Thiago; Duarte, Marta M. M. F.; Morsch, Vera M.; Schetinger, Maria R. C.; Alves, Leucio C.; Tinucci-Costa, Mirela [UNESP]; Da Silva, Aleksandro S. (Elsevier B. V., 2015)
Dogs are the main host of Leishmania infantum, and the clinical presentation may range from asymptomatic to systemic manifestations. The immune mechanisms in infected, but clinically healthy dogs, prevails Th1 response mediated by cytokines. In this sense, adenosine deaminase (ADA) and butyrylcholinesterase (BChE) are considered as key enzymes in several physiological processes, including the modulation of inflammatory process. Considering the variable immune response against Leishmania and the known participation of ADA and BChE, the aim of this study was to assess the relation between these two enzymes with the inflammatory response as well as hepatic function in dogs naturally infected with L. infantum. For this purpose, the activity of ADA and BChE was assessed in sera of 24 dogs naturally infected with L. infantum, plus 17 healthy dogs. The naturally infected dogs had clinical signs compatible with leishmaniasis and sera activities of ADA (P<0.01) and BChE (P<0.05) decreased, when compared to the healthy group. The reduction of ADA activity probably represented an effect on inflammatory response, especially due to the decreased hydrolysis of extracellular adenosine, might in order to protect against tissue damage and, also, setting a down-regulation on pro-inflammatory cytokines. BChE enzyme had no effect on modulating the immune response in leishmaniasis, but it decreased, a fact may related to deficiency of synthesis in the liver. Therefore, ADA and BChE activities reduced probably in order to protect against extra tissue damage and due failure in synthesis, respectively.
Keywords: Ada; Bche; Cytokines; Leishmania